LOGISTICAL PROBLEMS OF MOVING MEDICINES AND PHARMACEUTICALS ACROSS THE CUSTOMS BORDER IN PANDEMIC CONDITIONS - G. Panaedova; T. Kulagovskay (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the current state of the pharmaceutical market of the Russian Federation, the dynamics of the import of medicines, the specifics of the activities of customs logistics, the problems of improving its development in pandemic conditions. Methods ofstate regulation of drugs and pharmaceutical substances have been investigated and their effectiveness has been assessed. An analysis of the foreign trade turnover ofpharmaceutical products, the structure and dynamics of imports to the Russian Federation was carried out, an assessment of its impact on drug supply was given. The features of the movement of drug products from European countries to the Russian Federation and the procedure for customs clearance of pharmaceutical products in pandemic conditions were revealed. Logistics features were identified and recommendations were proposed aimed at providing the national market with medicinal products.